2005
DOI: 10.1080/10623320500227283
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-Mesenchymal Transition Occurs during Embryonic Pulmonary Artery Development

Abstract: Pulmonary vascular remodeling is a process generally associated with pulmonary hypertension that involves intimal thickening, medial hyperthrophy, and plexiform lesions. Morphological studies during pulmonary hypertension have indicated that intimal thickening consists of immature smooth muscle cells (SMCs) associated with determined extracellular matrix components, suggesting an important role for these cells in vascular lesions. Controversy exists regarding the nature and origin of the cells conforming the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 25 publications
0
78
0
Order By: Relevance
“…Arciniegas reported that endothelial cells transdifferentiated into SMCs vessel walls in the advanced stages of chicken embryo development. And then, they demonstrated that embryonic pulmonary endothelial cells underwent a transition to mesenchymal cells and participated in intimal thickening formation and pulmonary vascular remodeling (9). During maturation of dorsal aorta in quail, endothelial cells experimentally labeled with a wheat germ agglutinin-colloidal gold marker were shown to differentiate into subendothelial mesenchymal cells that were positive for both endothelial and mural markers in the aortic wall (10).…”
Section: Endmt In Embryonic Developmentmentioning
confidence: 99%
“…Arciniegas reported that endothelial cells transdifferentiated into SMCs vessel walls in the advanced stages of chicken embryo development. And then, they demonstrated that embryonic pulmonary endothelial cells underwent a transition to mesenchymal cells and participated in intimal thickening formation and pulmonary vascular remodeling (9). During maturation of dorsal aorta in quail, endothelial cells experimentally labeled with a wheat germ agglutinin-colloidal gold marker were shown to differentiate into subendothelial mesenchymal cells that were positive for both endothelial and mural markers in the aortic wall (10).…”
Section: Endmt In Embryonic Developmentmentioning
confidence: 99%
“…13,14 Also, it has been proposed that the nuclear localization of both p50 and p65 subunits in intimal cells of atherosclerotic lesions is an indicator of NFκB activity. [20][21][22][23][24][25] We therefore also examined by double immunoperoxidase staining whether p50, p65 or IKKα were present at the nucleus of those cells that expressed α-SM actin at days E12-E14 of development, when the intimal thickening is evident.…”
Section: Resultsmentioning
confidence: 99%
“…12 It may involve several regulated steps: cell spreading, cell separation or loss of cell-cell contacts or adherence junctions, proteases, cytokine and growth factor synthesis and secretion, ECM remodeling, membrane receptor expression, cytoskeletal organization, cell separation from the substratum (cell detachment) and cell migration and differentiation. 12 Of particular significance, intimal thickening formation involving EndoMT has been described in both aortic 13 and pulmonary artery wall 14 during advanced stages of chicken embryo development and correlated with an increase in blood pressure that occurs during these stages. Nevertheless, the mechanisms by which endothelial transformation occurs, as well as the signals controlling this process, are only beginning to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Fixed and permeabilized cells were processed for immunofluorescence as previously described (Arciniegas et al, 2005) using the following antibodies: a mouse monoclonal antibody (mab) anti-human integrin 3 (GPIIIa, CD61) and a mab anti-chicken integrin 1 www.intechopen.com …”
Section: Immunofluorescencementioning
confidence: 99%
“…Fixed cells were processed for immunoperoxidase as described previously (Arciniegas et al, 2005) using a rabbit pab raised against a short amino acid sequence containing phosphorylated Tyr845 of EGFR of human origin, and a rabbit pab raised against a short amino acid sequence containing phosphorylated Tyr877 of ErbB2/Neu of human origin (Santa Cruz Biotechnology). The images were captured using the Image Pro Plus software program.…”
Section: Immunoperoxidasementioning
confidence: 99%